2023
DOI: 10.3390/jcm12041681
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference of Central Nervous System-Regulated Hormones in COVID-19: A Bidirectional Two-Sample Mendelian Randomization Study

Abstract: We assessed the causal association of three COVID-19 phenotypes with insulin-like growth factor 1, estrogen, testosterone, dehydroepiandrosterone (DHEA), thyroid-stimulating hormone, thyrotropin-releasing hormone, luteinizing hormone (LH), and follicle-stimulating hormone. We used bidirectional two-sample univariate and multivariable Mendelian randomization (MR) analyses to evaluate the direction, specificity, and causality of the association between CNS-regulated hormones and COVID-19 phenotypes. Genetic inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…These findings are in alignment with previous cross-sectional studies [ 12 , 62 , 63 , 64 ], indicating that alterations in isolated thyroid function indicators alone may not be sufficient to reliably predict the development of viral pneumonia or COVID-19. Prior to this study, four MR investigations examined the relationship between thyroid hormones and COVID-19, utilizing data from the fifth round of the Human Genetics of Infectious Diseases (HGI) releases [ 31 , 65 , 66 , 67 ]. In 2023, Sun et al employed an MR model to assess the causal link between TSH levels and three COVID-19 phenotypes and concluded that there was no association between TSH and COVID-19 [ 65 ], a conclusion consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in alignment with previous cross-sectional studies [ 12 , 62 , 63 , 64 ], indicating that alterations in isolated thyroid function indicators alone may not be sufficient to reliably predict the development of viral pneumonia or COVID-19. Prior to this study, four MR investigations examined the relationship between thyroid hormones and COVID-19, utilizing data from the fifth round of the Human Genetics of Infectious Diseases (HGI) releases [ 31 , 65 , 66 , 67 ]. In 2023, Sun et al employed an MR model to assess the causal link between TSH levels and three COVID-19 phenotypes and concluded that there was no association between TSH and COVID-19 [ 65 ], a conclusion consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, four MR investigations examined the relationship between thyroid hormones and COVID-19, utilizing data from the fifth round of the Human Genetics of Infectious Diseases (HGI) releases [ 31 , 65 , 66 , 67 ]. In 2023, Sun et al employed an MR model to assess the causal link between TSH levels and three COVID-19 phenotypes and concluded that there was no association between TSH and COVID-19 [ 65 ], a conclusion consistent with our research. Compared to previous studies, our analysis utilized data from the seventh round, which had a larger sample size than the fifth round.…”
Section: Discussionmentioning
confidence: 99%
“…15 MVMR analysis can be carried out to identify and elucidate potential confounding factors. 16 This study used the UVMR method based on GWAS data to analyse whether there is a causal effect between psoriasis vulgaris and dementia. Moreover, MVMR analyses were conducted to investigate the potential confounding effect of platelet-related indices, Vitamin D level and 25 hydroxyvitamin D level on the causal association between psoriasis vulgaris and VaD.…”
Section: Introductionmentioning
confidence: 99%
“…MVMR can estimate the causal effects of multiple exposures which may be closely interrelated 15 . MVMR analysis can be carried out to identify and elucidate potential confounding factors 16 …”
Section: Introductionmentioning
confidence: 99%